Islamic Economic Empowerment Model During The Covid 19 Pandemic In Lazismu Surakarta - Saiev Dzaky El Kemal; Qurroh Ayuniyyah; Rio Erismen Armen; Mufti Maula Alfani (Journal of Islamic Economic Laws, 2022)
The COVID 19 pandemic is a new challenge for the Islamic economy to be able to be a solution to various problems that arise due to the impact of the spread of the COVID 19 virus in every community. The impact caused by the pandemic is not only on the health aspect but also on the economic aspect. This study aims to find out what are the models of economic empowerment in the Islamic Economy that can be done during the COVID 19 pandemic. The research method used is qualitative descriptive. This method explains the phenomena that occur in society and then a conclusion is drawn. The results of this study are the first, the empowerment model carried out by LAZISMU Surakarta during the pandemic has been in accordance with government rules, namely the funds are distributed to those who are entitled to receive it legally Islamic and also pay attention to the scale of community priorities. Second, the category of consumptive empowerment is 11% greater than productive empowerment. Third, the benefits obtained by the community from consumptive empowerment are greater when the number of pandemic cases is increasing, while when the trend of confirmed case numbers is falling, productive empowerment is more expected by the community. Fourth, the Islamic Economy is still able to play a role in tackling emergencies such as the COVID 19 pandemic. This is evidenced through LAZISMU Surakarta which has been able to empower people's funds professionally.